Macrocyclic lactones in antiparasitic therapy [ - Rew, Robert. S.; Vercruysse, J (CABI, 2002)
"Parasitic diseases are the most widespread of all of the major diseases, currently affecting innumerable domestic animals and humans. Macrocyclic lactones are chemical compounds that represent the main treatment for these parasitic diseases, not only for helminth infections, but also for a number of major ectoparasitic infestations." "A previous book published in 1989 provided a comprehensive view of one of the macrocyclic lactones. The present book updates previous information and expands to provide new information generated on the entire class of compounds together with detailed coverage of the basic science of these drugs and their mode of action, as well as their clinical use in farm and companion animals and in humans. The contents include chemistry and mode of action, pharmacology, toxicology, ecology and efficacy, use in large and small animals and in humans, and resistance against macrocyclic lactones. The book will be of interest to those working within the areas of parasitology, pharmacology, and veterinary and human medicine."--Jacket.